2015
DOI: 10.1097/aud.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonlinear Frequency Compression on ACC Amplitude and Listener Performance

Abstract: Objectives Nonlinear frequency compression is a signal processing technique used to increase the audibility of high frequency speech sounds for hearing aid users with sloping, high frequency hearing loss. However, excessive compression ratios may reduce spectral contrast between sounds and negatively impact speech perception. This is of particular concern in infants and young children who may not be able to provide feedback about frequency compression settings. This study explores use of an objective cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…While our focus has been on Hybrid CI users, the techniques we describe have and could be adapted to address a wide range of potentially clinically relevant questions. For example, Kirby and Brown (in press) report measures of the ACC evoked using ripple noise stimuli with contrasting spectra, similar to those described by Won and colleagues (2011). They showed that AAC amplitude measures were affected by the use of frequency compression in a hearing aid and that changes in the frequency compression ratio directly influenced the amplitude of the ACC recorded using rippled noise stimuli.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…While our focus has been on Hybrid CI users, the techniques we describe have and could be adapted to address a wide range of potentially clinically relevant questions. For example, Kirby and Brown (in press) report measures of the ACC evoked using ripple noise stimuli with contrasting spectra, similar to those described by Won and colleagues (2011). They showed that AAC amplitude measures were affected by the use of frequency compression in a hearing aid and that changes in the frequency compression ratio directly influenced the amplitude of the ACC recorded using rippled noise stimuli.…”
Section: Discussionmentioning
confidence: 77%
“…They showed that AAC amplitude measures were affected by the use of frequency compression in a hearing aid and that changes in the frequency compression ratio directly influenced the amplitude of the ACC recorded using rippled noise stimuli. While the current study describes essentially negative findings, our hope is the techniques similar to those used in this report and in the Won et al (2011) and the Kirby and Brown (in press) studies will serve as a small step toward identifying a larger role for CAEP in clinical practice.…”
Section: Discussionmentioning
confidence: 84%
“…This method has theoretical advantages in comparison with other frequency-lowering approaches. It does not introduce distortion of vowel formant ratios by shifting the second formant as can occur with frequency compression settings with a start frequency below 2000 Hz (Perreau et al, 2013;Kirby and Brown, 2015). It also has a narrower destination band relative to transposition, reducing the likelihood of the shifted speech sounds masking other speech information already present in that band.…”
mentioning
confidence: 99%
“…It can be evoked using a passive listening paradigm. It has been successfully recorded using spectrally complex acoustic stimuli presented in the sound field and processed by a hearing aid or a cochlear implant (Brown et al, 2008; Friesen & Tremblay, 2006; Kirby & Brown, 2015). Previous work from our lab and others has shown that changes in these cortical auditory evoked potentials may parallel changes in perception associated with training (Brown et al, 2014; Tremblay & Kraus, 2002).…”
Section: Training Program Evaluationmentioning
confidence: 99%